Polyamine Catabolism in Plants: A Universal Process With Diverse Functions - Wang, Wei; Paschalidis, Konstantinos; Feng, Jian-Can; Song, Jie; Liu, Ji-Hong (Frontiers in Plant Science, 2019)
Polyamine (PA) catabolic processes are performed by copper-containing amine oxidases (CuAOs) and flavin-containing PA oxidases (PAOs). So far, several CuAOs and PAOs have been identified in many plant species. These enzymes exhibit different subcellular localization, substrate specificity and functional diversity. Since PAs are involved in numerous physiological processes, considerable efforts have been made to explore the functions of plant CuAOs and PAOs during the recent decades. The stress signal transduction pathways usually lead in increase of the intracellular PA levels, which are apoplastically secreted and oxidized by CuAOs and PAOs, with parallel production of H2O2. Depending on the levels of the generated H2O2, high or low, respectively, either programmed cell death (PCD) occurs or H2O2 is efficiently scavenged by enzymic/non-enzymic antioxidant factors that help plants coping with abiotic stress, recruiting different defense mechanisms, as compared to biotic stress. Amine and PA oxidases act further as PA back-converters in peroxisomes, also generating H2O2, possibly by activating Ca2+ permeable channels. Here, the new research data are discussed on the interconnection of PA catabolism with the derived H2O2, together with their signaling roles in developmental processes, such as fruit ripening, senescence, and biotic/abiotic stress reactions, in an effort to elucidate the mechanisms involved in crop adaptation/survival to adverse environmental conditions and to pathogenic infections.